Probabilistic load model in power system reliability assessment / Khairul Naim Husaini - Husaini, Khairul Naim (2009)
This final year project describes a proposed research in power system reliability assessment by using a method probabilistic load model. The proposed methodology will attempt to minimize the complicated method and relatively difficult procedure to obtain reliability index, to ensure system's maintain reliability at high level, to know the system position whether is stable or not and beneficial in term of cost, energy, time saving and increase efficiency of supplying the electricity. In this proposed methodology states are sampled according to the probabilistic models of system components whereas system component outages can still be modeled using Markov model. This methodology will identify and analyze the system component outages and outcomes of this resultant analysis will yield a reliability index which is Expected Energy Not Supplied (EENS) in a power system that may be used to describe system's reliability itself and the effect of the load curve model.